A new measurement of the stellar mass density at z approximate to 5: Implications for the sources of cosmic reionization - Stark, D; Bunker, A; Ellis, R; Eyles, L; Lacy, M (Institute of Physics Publishing, 2007)
We present a new measurement of the integrated stellar mass per comoving volume at redshift 5 determined via spectral energy fitting drawn from a sample of 214 photometrically selected galaxies with z′850LP < 26.5 in the southern GOODS field. Following recent procedures introduced by Eyles et al., we estimate stellar masses for various subsamples for which reliable and unconfused Spitzer IRAC detections are available. A spectroscopic sample of 14 of the most luminous sources with z̄ = 4.92 provides a firm lower limit to the stellar mass density of 1 × 106 Ṁ Mpc -3. Several galaxies in this subsample have masses of order 10 11 M⊙, implying that significant earlier activity occurred in massive systems. We then consider a larger sample whose photometric redshifts in the publicly available GOODS-MUSIC catalog lie in the range 4.4 < z < 5.6. Before adopting the GOODS-MUSIC photometric redshifts, we check the accuracy of their photometry and explore the possibility of contamination by low-z galaxies and low-mass stars. After excising probable stellar contaminants and using the z′850LP - J color to exclude any remaining foreground red galaxies, we conclude that 196 sources are likely to be at z ≃ 5. The implied mass density from the unconfused IRAC fraction of this sample, scaled to the total available, is 6 × 106 M ̇ Mpc-3. We discuss the uncertainties, as well as the likelihood that we have underestimated the true mass density. By including fainter and quiescent sources, the total integrated density could be as high as 1 × 107 Ṁ Mpc-3. Even accounting for 25% cosmic variance within a single GOODS field, such a high mass density only 1.2 Gyr after the big bang has interesting consequences for the implied past average star formation during the period when cosmic reionization is now thought to have taken place. Using the currently available (but highly uncertain) rate of decline in the star formation history over 5 < z < 10, a better fit is obtained for the assembled mass at z ≃ 5 if we admit significant dust extinction at early times or extend the luminosity function to very faint limits. An interesting consequence of the latter possibility is an abundant population of low-luminosity sources just beyond the detection limits of current surveys. As mass density estimates improve at z ≃ 5-6, our method is likely to provide one of the tightest constraints on the question of whether star-forming sources were responsible for reionizing the universe. © 2007. The American Astronomical Society. All rights reserved.